1024. Impact of Treatment Adherence on Efficacy of DTG/3TC and DTG + TDF/FTC: Pooled Analysis of the GEMINI 1 and 2 Clinical Trials. (31st December 2020) - Ait-Khaled, Mounir; Man, Choy; Sievers, Jorg; Grove, Richard; Wynne, Brian; Urbaityte, Rimgaile; van Wyk, Jean A; Madero, Juan G Sierra; Gulminetti, Roberto; Estrada, Vicente; Hagins, Debbie; Zolopa, Andrew; et al.
Abstract: Background: GEMINI 1 & 2 are global double-blind, multi-center phase III non-inferiority studies evaluating efficacy and safety of dolutegravir (DTG) + lamivudine (3TC) once daily in treatment-naive HIV-1-infected adults with Screening HIV-1 RNA ≤ 500, 000 c/mL (ClinicalTrials.gov: NCT02831673/NCT02831764). Participants were randomized 1:1 to treatment with DTG+3TC or DTG + tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC). The primary endpoint was the proportion of participants with plasma HIV-1 RNA < 50 c/mL at Week 48 (Snapshot algorithm). DTG+3TC was non-inferior to DTG+TDF/FTC at Weeks 48 and 96. Here we evaluate the impact of treatment adherence on Week 48 virologic response (VR) within the GEMINI trials as a post-hoc analysis. Methods: Adherence was estimated using pill counts data and categorized as follows: ≥ 90% vs < 90%. Week 48 VR was measured as % of participants with HIV-1 RNA < 50 c/mL by Food and Drug Administration Snapshot and by last on treatment viral load (VL) for the intention to treat–exposed population for which adherence could be derived. VR and differences between treatment arms within each adherence category were calculated along with exact unadjusted 95% confidence intervals. Results: 5% of participants had < 90% adherence in both treatment arms. Baseline VL and CD4+ cell counts were similar across adherence categories. VR was lower in the < 90% adherence group than the ≥ 90% group, but not different between the 2 treatment arms within the same adherence category: In the low adherence group, DTG+3TC VR was 69% compared to 65% in DTG+TDF/FTC arm by Snapshot and 91% and 85% respectively by last on treatment VL analysis (Table). Table. Conclusion: In the GEMINI studies, a lower Week 48 VR was observed in participants with < 90% adherence, but the impact of lower adherence on VR was similar in the DTG+3TC compared with DTG+TDF/FTC arms. One limitation of the analysis is the small number of participants in the lower adherence subgroup. However, the results add further information about the robustness of DTG+3TC compared to 3-drug DTG-containing regimens and may suggest similar regimen forgiveness. Disclosures: Mounir Ait-Khaled, PhD, ViiV Healthcare (Employee, Shareholder) Choy Man, BSc, ViiV Healthcare (Employee, Shareholder) Jorg Sievers, DPhil, ViiV Healthcare (Employee) Richard Grove, MSc, GSK/ViiV (Employee, Shareholder) Brian Wynne, MD, ViiV Healthcare (Employee) Rimgaile Urbaityte, MSc, GlaxoSmithKline (Employee, Shareholder) Jean A. van Wyk, MB, ChB, ViiV Healthcare (Employee, Shareholder) Debbie Hagins, MD, Gilead Sciences Inc. (Consultant, Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member)Janssen (Grant/Research Support)Merck (Consultant, Grant/Research Support, Advisor or Review Panel member)Viiv Healthcare (Consultant, Grant/Research Support, Advisor or Review Panel member) Andrew Zolopa, MD, ViiV Healthcare (Employee)